Antibacterial and antioxidant properties of phyto‐synthesized silver nanoparticles using Lavandula stoechas extract. (16th December 2019) - Mahmoudi, Reza; Aghaei, Saeed; Salehpour, Zeinab; Mousavizadeh, Ali; Khoramrooz, Seyed Sajjad; Taheripour Sisakht, Marzie; Christiansen, Gunna; Baneshi, Marzieh; Karimi, Bahman; Bardania, Hassan
Abstract : Due to environmentally friendly and cost‐ effective issues, biological methods for silver nanoparticles (AgNPs) synthesis are advantageous over chemical and physical ones. In this study, AgNPs synthesized using Lavandula stoechas extract as a reductant and its antioxidant capacity, antibacterial property and cytotoxicity effect were investigated. The phyto‐synthesized AgNPs were characterized using various analyses such as transmission electron microscopy (TEM), scanning electron microscopy (SEM), x‐ray diffraction (XRD) as well as Fourier transform infrared (FT‐IR). The prepared nanoparticles were spherical on shape with the size about 20–50 nm. Antibacterial studies through agar disk diffusion method confirmed the antibacterial potential of phyto‐synthesized AgNPs toward two clinical Staphylococus aureus and Pseudomonas aeruginosa bacteria, although MTT assay demonstrated that S. aureus (MIC = 125 μg/ml) was more susceptible to AgNPs than P. aeruginosa (MIC = 250 μg/ml). Moreover, the cytotoxicity assay of phyto‐synthezied AgNPs showed a low cytotoxic effect on RAW264 cell line at 62.5 μg/ml as an effective concentration. Also the considerable antioxidant capacity of the AgNPs confirmed through DPPH assay. Great antibacterial and antioxidant properties along with biocompatibility make the suggested phyto‐synthesized AgNPs a great candidate for different biomedical applications including wound healing. Abstract : AgNPs were Synthesized by using Lavandula stoechas hydroalcoholic extract and Characterized by using different analyses such as FT‐IR, XRD, TEM, SEM and UV‐Vis. Phytosynthesized AgNPs had high antibacterial activity against Pseudomonas aeruginosa and Staphylococcus aureus bacteria cells. Phytosynthesized AgNPs had high antioxidant capacity and low cytotoxicity effect on RAW264 cell line.